Community responses to biosecurity regulations during a biosecurity outbreak: An Auckland, New Zealand Case Study. Issue 1 (1st January 2021) - Ram, Rajesh
ABSTRACT: The destructive Queensland fruit fly (QFF), known to attack export varieties of New Zealand grown primary horticultural produce was discovered in February 2015 in the suburb of Grey Lynn, Auckland, New Zealand, resulting in a biosecurity crisis. Invasion ecology theory was used to understand measures put in place by the authorities in the community to control its spread. Community members in the fruit fly affected area were invited to take part in research. Seven different questions related to the QFF and wider environmental issues were the focus during interviews. Results showed that although the community cooperated with the authorities by following strict guidelines such as restricting the movement of QFF host material. Loss of privacy, a lack of information about the QFF and unfamiliarity with the term biosecurity were some issues reported by the community. Education, coupled with effective marketing about biosecurity, may increase community involvement in the biosecurity cause.